Effect of rumen escape amino acids and multiple TBA implants on feedlot performance of lightweight Holstein steer calves - B.J. Healy; Robert T. Brandt Jr.; Evan C. Titgemeyer (Kansas Agricultural Experiment Station Research Reports, 1995)
Two hundred forty Holstein steers (343 lb) were stratified by weight and allotted to one of eight treatment combinations in a 2 x 4 factorial arrangement. Main effects were implant (Synovex-S (S) or Synovex-S + Finaplix-S (SF) on day 0, 87, 168, and 238 and level of rumen escape amino acids (Smartamine-ML (SML) at 0, 5, 10, or 15 grams/head/day). These levels of SML supplied 0, 2.75, 5.5, and 8.25 g/day of Llysine and 0, .75, 1.5, and 2.25 g/day of DL-methionine. Steers implanted with SF gained 4% faster, had a 4% improvement in feed:gain, a lower dressing percentage, 12% less backfat, 3.4% more rib-eye area, a lower yield grade, less marbling, and fewer Choice grades (P<.05) compared to S-implanted steers. Overall feed intake and carcass weights were similar between S- and SF-implanted steers. Use of SML resulted in a linear decline in hot carcass weight (P<.10) and KPH (P<.05), with other carcass traits unaffected. Increasing the level of SML tended to increase feed intake (P<.15), and quadratically degraded feed:gain (P<.10). Repeated implants of SF did not improve carcass worth and the use of rumen escape amino acids did not improve performance, suggesting that the basal diet was not first-limiting in lysine and(or) methionine.
Keywords: Cattlemen& #x27; s Day; 1995; Kansas Agricultural Experiment Station contribution; no. 95-357-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 727; Beef; Estradiol; Trenbolone acetate; Rumen escape amino acids; Holstein; Steers